The Four verbal Patterns of Fi'aal, Fu'al, Fa'al, Fa'aali and Their Morphological Indications in Arabic - Seher Doğancı (Şarkiyat Mecmuası)
For previous linguistic scholars, Arabic grammar consists of general comparative rules that involve oral language texts. A special condition applies to these texts, such as having fluency, having the same samples in the language as examples, having usage in Arabic culture, and having been widely used to represent the Arabic language’s general grammar rules strongly. This study not only focuses on former Arabic linguistics and their opinions about verbal patterns such as fa ̒aal, fu ̒all, fi ̒aal, and fa ̒aali, but also gives extraordinary examples from the Quran and poets that former linguists have used as examples of morphology. In addition, other linguists have indicated Sibawayh’s optimality theory about verbal patterns for speaking performance and morphological structure to be acceptable. This study also aims using descriptive analysis to explain Arabic verbal patterns and their usage in the Arabic language, such as with fa ̒aal, fu ̒all, fi ̒aal, and fa ̒aali through examples from Quranic verses and poems in order to explain the topic. A shift of meaning is indicated to have occurred in these verbal patterns from their original meanings to figurative meanings in terms of the convergence and divergence of meaning. Moreover, the study examines the signs of verbal patterns as a form and fundamental. For example, former Arabic linguists such as Sibawayh, al-Suyûtî, Ibn al-Sarrāj, and Ibn Aqîl were determined to have their own ̒ opinions about the fa ̒aal verbal patterns in Arabic such as how these verbal patterns formed, their lack of morphological derivation, and their usage of Arabic.